What would the political philosophers do? An exploration of ideological perspectives on ‘athlete-centered’ reform - Otto, Kadence (Journal of Amateur Sport, 2016)
In this paper I explore how the values inherent in the political philosophies of libertarianism, capitalism, utilitarianism, and egalitarianism are manifest in big-time college athletics reform which places athletes’ rights as its highest value. The initial intent of the paper focuses on the use of Marx and Engels’ dialectical materialism as a way of framing the historical relationship between the NCAA and the athletes. Next, I turn to the main thrust of the paper which is to utilize the ideological inquiry approach to explore the overarching values inherent in the perspectives of John Locke, Adam Smith, John Stuart Mill, and John Rawls in an attempt to see more clearly how their perspectives are manifest in ‘athlete-centered’ reform. Lastly, I put forth that, based on the values inherent in the perspectives of the political philosophers, ‘athlete-centered’ reform begins with liberty for the athlete, which is assured by right, just, and democratic institutions, and is secured by an athlete association.